Yahoo Answers: Answers and Comments for Math helppp? [Mathematics]
Copyright © Yahoo! Inc. All rights reserved.
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
From Hello2098
enGB
Tue, 22 Oct 2019 00:49:31 +0000
3
Yahoo Answers: Answers and Comments for Math helppp? [Mathematics]
292
38
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://s.yimg.com/zz/combo?images/emaillogouk.png

From David: Pull out the obvious common factor of 3ab
3ab(...
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
Tue, 22 Oct 2019 01:13:39 +0000
Pull out the obvious common factor of 3ab
3ab(a³  b³)
A potentially useful rule is that any polynomial of the form a^n  b^n has a factor a  b.
Then factoring out by comparing coefficients, we get
3ab(a³  b³) = 3ab(a  b)(a² + ab + b²)
We can't factor any further without complex numbers
With complex numbers, the result is:
3/4ab(a  b)(2b + a(1  i√3))(2b + a(1 + i√3))

From Krishnamurthy: 3a^4b  3ab^4
= 3ab(a  b)(a^2 + ab + b^2)
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
Tue, 22 Oct 2019 16:26:06 +0000
3a^4b  3ab^4
= 3ab(a  b)(a^2 + ab + b^2)

From Como: 
3 a b ( a³  b³ )
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
Tue, 22 Oct 2019 12:02:37 +0000

3 a b ( a³  b³ )

From sepia: 3a^4b  3ab^4
= 3ab(a  b)(a^2 + ab + b^2)
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
Tue, 22 Oct 2019 02:39:22 +0000
3a^4b  3ab^4
= 3ab(a  b)(a^2 + ab + b^2)

From Nadia: Pull out common things. Common to both terms a...
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
https://uk.answers.yahoo.com/question/index?qid=20191022004931AAwy7cf
Tue, 22 Oct 2019 01:00:24 +0000
Pull out common things. Common to both terms are 3, a, and b.
3ab(a^3  b^3)